A concise history of Germany - Fulbrook, Mary 1951- (Cambridge Univ. Press, 1990)
Examines the social, political, and cultural changes in Germany from medieval times to the present.
Keywords: Geschichte; Allemagne - Histoire; Deutschland; Germany -- History